State of the art of the evaluation of public policy on territorialenvironmental planning in Colombia - Garcia-Cabana, Andrea Carolina (2021)
The evaluation of public policies has posed different challenges that seek to improve the performance of public management to achieve this it does so through the systematic measurement of theoperation or impact of public programs or policies, which when compared with implicit or explicitstandards allows to contribute to their improvement (Weiss, 1998). This article reviews the stateof the literature, regarding the evaluation of public policies for environmental territorial planningin Colombia. A methodical review was made of the articles published in journals indexed in thedatabases SciELO.org and EBSCO Information Services in the period between 1995 and 2020. Asa result of the research, the state of the art of the evaluation of public policies on the specific issueof territorial environmental planning in Colombia was obtained, and some recommendations wereestablished to strengthen the dissemination of the public policy evaluation processes in the country